2016
DOI: 10.3390/safety2020012
|View full text |Cite
|
Sign up to set email alerts
|

Quads, Farmers 50+ Years of Age, and Safety in Australia

Abstract: Abstract:Quads are the leading cause of fatal non-intentional injuries on Australian farms. Due to normal age-related physiological and cognitive changes, farmers 50-years of age and above are at increased risk when using quads. This study identifies a non-statistically significant increasing trend for fatal quad incidents involving this cohort in Australia. It is contended that these vehicles are not "fit-for-purpose" for many typical agricultural tasks more broadly and that the ageing process further exacerb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…These results largely support existing data on farm fatalities, illustrating that older individuals are particularly susceptible to on‐farm injury incidents 6,14,15 . While no definitive rationale for the higher severity of injuries sustained in the older cohort can be provided, it might be contended that the normal physiological and cognitive changes that are associated with the ageing process underpin these incidents.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These results largely support existing data on farm fatalities, illustrating that older individuals are particularly susceptible to on‐farm injury incidents 6,14,15 . While no definitive rationale for the higher severity of injuries sustained in the older cohort can be provided, it might be contended that the normal physiological and cognitive changes that are associated with the ageing process underpin these incidents.…”
Section: Discussionsupporting
confidence: 76%
“…While there is no standard definition that defines ‘older farmers,’ 5,8,22 previous Australian studies have used 50 years as an inclusive lower age cut‐off point 14,15 . Hence, a similar approach was adopted with this study, resulting in two age group cohorts (15‐49 years and 50+ years).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Safety concerns were first highlighted in the early 2000s when a study of trends in farm deaths illustrated that while deaths from tractor rollovers had decreased by 74% between 1982–84 and 2001–04, quad‐related incidents had increased nearly 13‐fold 1 . Since this study there have been several reports which all identified a significant fatality burden (especially in relation to agricultural work) 6–10 …”
Section: Location 2010–15 2016–20 Total %mentioning
confidence: 80%
“…1 Since this study there have been several reports which all identified a significant fatality burden (especially in relation to agricultural work). [6][7][8][9][10] Previous Australian data indicated a statistical difference in the nature of work and non-work fatalities, with work incidents significantly more likely to involve rollovers and asphyxiation/crush injuries. In contrast, non-work cases were more likely to involve non-rollover incidents and head injuries.…”
mentioning
confidence: 99%